Development of hotel tourism services and their impact on attraction Tourist in Lattakia Governorate - ناصر لميس (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Lattakia Governorate is one of the most important as tourist attraction area in Syria, because of its natural and human characteristics that are considered as attractive factors for the tourism industry. In addition to the strong relationship between tourism activities and tourism services, i.e the tourism services of all kinds cause growth and prosperity of tourism, so we can say that accommodation services in general and hotels in particular constitute an important pillar of the tourist activity. The characteristics, types, and methods of marketing tourism services was studied at this research. The study was also about tourism services in Lattakia and classifying hotels and their services. The study included hotels and nights guests, and development of tourism services and its role in attractions, We concluded that there are several models for accommodation services in Lattakia, and the development and multiplicity of hotel services contribute to attractions, increase tourism revenues and job opportunities. Hotel occupancy rates in Lattakia have reached 86% during the summer tourist season.